Differentiation of Positional Isomers of Propyl Alcohols Using Filament-Induced Fluorescence*Supported by the National Natural Science Foundation of China under Grant Nos 61427816 and 61235003, the Research Fund for the Doctoral Program of Higher Education of China under Grant No 20130061110047, and the Open Fund of the State Key Laboratory of High Field Laser Physics. (May 2016) - Wei 魏, Xiang-Ye 祥野; Tu 涂, Zhi-Wei 志伟; Liu 刘, Chang 畅; Li 李, He-Long 贺龙; Xu 徐, Huai-Liang 淮良
Abstract : We experimentally demonstrate the recognition of positional isomers of propyl alcohol vapor through nonlinear fluorescence induced by high-intensity femtosecond laser filaments in air. By measuring characteristic fluorescence of n-propyl and isopropyl alcohol vapors produced by femtosecond filament excitation, it is found that they show identical spectra, that is, those from molecular bands of CH, C2, NH, OH and CN, while the relative intensities are different. By comparing the ratios of the CH and C2 signals, the two propyl alcohol isomers are differentiated. The different signal intensities are ascribed to different ionization potentials of the two isomer molecules, leading to different production efficiencies of fluorescing fragments.